Implementasi Notaris Yang Dijatuhkan Sanksi Sebagai Pelaku Tindak Pidana - Nanda Yuliska; Rasji Rasji (LPPM Universitas Ekasakti Padang, 2023)
The issue involving notary Hendrik Jaury, accused of committing corruption, resulted in a 2-year prison sentence and a fine of Rp50,000,000,- based on the Decision of the District Court of Makassar. The second case involves Hendrik Jaury as a suspect in alleged fraud and embezzlement of property ownership certificates, according to the Investigation Order from the Makassar City Police on March 11, 2021. The defendant was reported by Muhammad Ali for not completing the promised certificate affairs since 2011, and investigators designated Hendrik Jaury as a suspect. A problem arises concerning the provisions of the Notary Position Law, which does not impose legal consequences on the professional status of a notary involved in criminal acts with a punishment of less than 5 years. The research findings suggest that notaries engaged in criminal activities should face sanctions to maintain the integrity and professionalism of the notary profession. The legal enforcement process against notaries violating regulations or engaging in criminal activities is governed by Article 13 of the Notary Position Law. The Notary Ethics Council is responsible for ethical aspects and professional standards, taking disciplinary action through an ethical trial process, providing the notary an opportunity to defend themselves and explain the reasons for the violation.